Differential Diagnosis of Metatarsalgia - Afonso, P Diana; Britto, Sabrina Veras; Spritzer, Charles E; Martins E Souza, Patrícia (Seminars in musculoskeletal radiology, 2023)
Lesser (or central) metatarsalgia is defined as pain in the forefoot under or around the lesser metatarsals and their respective metatarsophalangeal joints. Two common causes of central metatarsalgia are Morton's neuroma (MN) and plantar plate (PP) injury. Because both clinical and imaging features overlap, establishing the correct differential diagnosis may be challenging. Imaging has a pivotal role in the detection and characterization of metatarsalgia. Different radiologic modalities are available to assess the common causes of forefoot pain, so the strengths and weakness of these imaging tools should be kept in mind. It is crucial to be aware of the pitfalls that can be encountered in daily clinical practice when dealing with these disorders. This review describes two main causes of lesser metatarsalgia, MN and PP injury, and their differential diagnoses.